2′‐Hydroxycinnamaldehyde inhibits proliferation and induces apoptosis via signal transducer and activator of transcription 3 inactivation and reactive oxygen species generation. Issue 1 (20th November 2018) - Yoon, Yae Jin; Kim, Young‐Hwan; Lee, Yu‐Jin; Choi, Jiyeon; Kim, Cheol‐Hee; Han, Dong Cho; Kwon, Byoung‐Mog
Abstract : Inhibition of the signal transducer and activator of transcription 3 (STAT3) signaling pathway is a novel therapeutic strategy to treat human cancers with constitutively active STAT3. During the screening of natural products to find STAT3 inhibitors, we identified 2′‐hydroxycinnamaldehyde (HCA) as a STAT3 inhibitor, which was isolated from the stem bark of Cinnamomum cassia . In this study, we found that HCA inhibited constitutive and inducible STAT3 activation in STAT3‐activated DU145 prostate cancer cells. HCA selectively inhibited the STAT3 activity by direct binding to STAT3, which was confirmed by biochemical methods, including a pull‐down assay with biotin‐conjugated HCA, a drug affinity responsive target stability (DARTS) experiment and a cellular thermal shift assay (CETSA). HCA inhibited STAT3 phosphorylation at the tyrosine 705 residue, dimer formation, and nuclear translocation in DU145 cells, which led to a downregulation of STAT3 target genes. The downregulation of cell cycle progression and antiapoptosis‐related gene expression by HCA induced the accumulation of cells in the G0/G1 phase of the cell cycle and then induced apoptosis. We also found that reactive oxygen species (ROS) were involved in the HCA‐induced inhibition of STAT3 activation and cell proliferation because the suppressed p‐STAT3 level was rescued by glutathione or N‐acetyl‐L‐cysteine treatment, which are general ROS inhibitors. These results suggest that HCA could be a potent anticancer agent targeting STAT3‐activated tumor cells. Abstract : 2′‐Hydroxycinnamaldehyde inhibits STAT3 activation and cell proliferation through STAT3‐dependent and ROS‐dependent pathways. 2′‐Hydroxycinnamaldehyde is highly effective in prostate cancer cells with activated‐STAT3 and also suppressed DU‐145 tumor growth in an animal model. 2′‐Hydroxycinnamaldehyde has low toxicity against normal human cells and selective toxicity toward cancer cells.